Childhood abuse experiences and their relationship to video game addiction among a sample of secondary school students in Damascus schools. (Damascus University Journal of educational and Psychologyical sciences, 2026)
This research aims to identify the relationship between childhood abuse experiences and electronic game addiction among a sample of secondary school students in Damascus schools; their number reached (560) male and female students. The scales of abuse experiences and electronic game addiction were used to answer the research questions and hypotheses. A set of results was reached, the most prominent of which are: There is a above average level of abuse experiences and electronic game addiction among the study sample members, and there is a positive relationship between both abuse experiences and electronic game addiction, and there are statistically significant differences between the study sample members on the abuse experiences scale according to the gender variable, and the differences were in favor of females, while the differences on the same scale were not significant according to the variable of the educational level of the parents, in addition to the presence of statistically significant differences between the study sample members on the electronic game addiction scale according to the variables of gender and the educational level of the parents, the differences were in favor of males, and students from uneducated families.
Keywords: Abuse experiences; video game addiction; adolescents; high school students